2014
DOI: 10.1016/j.chemgeo.2014.09.010
|View full text |Cite
|
Sign up to set email alerts
|

The role of Fe(III) bioreduction by methanogens in the preservation of organic matter in smectite

Abstract: Organic matter in sediments is largely associated with clay minerals and can be preserved over geological time. However, microbial activity can possibly influence this association and release organic matter from clay minerals via reductive or oxidative dissolution of clay minerals. In this study, the relationship between bioreduction of structural Fe(III) in smectite and organic matter release from smectite structure was investigated. A model organic compound, 12-aminolauric acid (ALA) was intercalated into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 70 publications
0
14
1
Order By: Relevance
“…26 Nontronite contains 21.2% total Fe, 98% of which is Fe(III). 26 Most of the structural Fe in smectite minerals is redoxactive. 27 Reduced montmorillonite and nontronite are capable of producing abundant •OH upon oxygenation, and the yield of • OH is positively correlated with oxidation of structural Fe(II).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…26 Nontronite contains 21.2% total Fe, 98% of which is Fe(III). 26 Most of the structural Fe in smectite minerals is redoxactive. 27 Reduced montmorillonite and nontronite are capable of producing abundant •OH upon oxygenation, and the yield of • OH is positively correlated with oxidation of structural Fe(II).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Two smectite minerals, montmorillonite (SWy-2) and nontronite (NAu-2), were chosen in this study. Montmorillonite is widely distributed in soils and sediments, and it contains 2.3% total Fe, 97% of which is Fe­(III) . Nontronite contains 21.2% total Fe, 98% of which is Fe­(III) .…”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This correlation suggests that the expandable internal surface of smectite (i.e., interlayer region) can sequester large amounts of molecular-scaled OM (Keil and Mayer, 2014; Kennedy and Wagner, 2011; however, see discussion in Mahamat Ahmat et al, 2016). Indeed, it has been suggested that enhanced organic matter preservation in sediments is largely due to increased smectite abundance in sedimentary record through geological time (Kennedy et al, 2006): organic matter, once associated with smectite-rich sediments, would be physically protected against microbial oxidation (see details in Keil and Mayer, 2014;Mahamat Ahmat et al, 2016Zhang et al, 2014). However, as reminded above, smectite can also bring reactive iron, which will impact OM preservation: first, iron oxi-hydroxides are electron acceptors used by bacteria during OM remineralization; an input of reactive iron may thus fuel OM-consuming bacteria.…”
Section: Iron and Clay-mineral Assemblagesmentioning
confidence: 99%
“…The enrichment of Al in NAu-2 after Fe(III) bioreduction was frequently reported in previous studies but was empirically understood as mainly being integrated into the NAu-2 crystal (mainly substitutes the tetrahedral Si sheet). 56,66,67 However, if Al only stayed within the tetrahedral sheet as Si did, both Al and Si signals would show a relatively high intensity in the ToF-SIMS pattern of BR-NAu-2 (i.e., similar to the situation of Figure 1a), which was not observed in either positive or negative ion spectra, suggesting that an Al-rich layer with some organic matter stays on NAu-2 surfaces over the Si layer (similar to Figure 1f). Considering that no external Al and K sources were added to the experiment, thus either a dissolution/recrystallization or a partial dissolution/redeposition process occurred in NAu-2 particles, leading to the formation of an Al-rich layer on basal surfaces.…”
Section: ■ Results and Discussionmentioning
confidence: 99%